COMPARISON ANALYSIS OF SAW AND SMART METHODS DECISION SUPPORT SYSTEMS IN SELECTIONS ONLINE TRANSPORTATION IN CITY COMMUNITIES BANDUNG - Habibi, Chairul; Yasyfa, Irtsa; Budiman, Budiman (International Journal of Global Operations Research, 2023)
Online transportation is transportation based on a particular application, where consumers order a means of transportation through an application system on a smartphone. This change in lifestyle is used by business actors to start business competition in the online transportation business. In the competition regarding price, convenience, driver courtesy, and satisfaction, there are various kinds of online transportation including Gojek, Grab, Maxim, and InDriver. In the end, this becomes a consideration for the selection of online transportation for the people of Bandung City. To overcome these problems, a Decision Support System was developed using 5 criteria including: Ease, Service Quality, Product Quality, Price and Emotional. Comparative analysis between the Simple Additive Weighting (SAW) and Simple Multi Attribute Technique (SMART) methods was conducted to find out how well the level of relevance of each method was to real conditions. Based on the ranking results from the questionnaire of 100 respondents from the Bandung City community, it is known that the distance difference between the rankings in the SAW method is 0.994 and the SMART method is 0.92. Thus, it can be concluded that the SAW method is considered relatively more relevant to be recommended in this type of case than the SMART method.